OPTIMALISASI LAYANAN PENELUSURAN SUMBER-SUMBER INFORMASI UNTUK MENDUKUNG PENULISAN KARYA ILMIAH DOSEN DAN MAHASISWA DI PERGURUAN TINGGI - Dian Hapsari (Jurnal Pustaka Ilmiah, 2016)
Publication of scientific papers for lecturers and students is a demand that can not be avoided. In order to find information as an ingredient in the manufacture of scientific work, the necessary sources of quality information and reliable. The library, in this case the librarian must be responsive and observant in seeing user needs. One way that can be done by librarians in providing information relating to the publication of scientific works of faculty and students is by providing search services information sources. To be able to do it optimally, it needs the capability to master the sources of information, including how to use search facilities and information search strategy. Thus, the term college library as the heart really can be realized with the maximum.